2017
DOI: 10.3390/ijerph14101245
|View full text |Cite
|
Sign up to set email alerts
|

Patient Aggression and the Wellbeing of Nurses: A Cross-Sectional Survey Study in Psychiatric and Non-Psychiatric Settings

Abstract: Wellbeing of nurses is associated with patient aggression. Little is known about the differences in these associations between nurses working in different specialties. We aimed to estimate and compare the prevalence of patient aggression and the associations between patient aggression and the wellbeing of nurses in psychiatric and non-psychiatric specialties (medical and surgical, and emergency medicine). A sample of 5288 nurses (923 psychiatric nurses, 4070 medical and surgical nurses, 295 emergency nurses) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 54 publications
(78 reference statements)
3
68
0
3
Order By: Relevance
“…It is important that all violent incidents are correctly reported for good management or prevention of violence. In our study, it was found that 32% of the nurses were exposed to physical violence and 65% had psychological violence at a similar rate with other studies . In contrast, the rate of reporting physical violence was 69%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is important that all violent incidents are correctly reported for good management or prevention of violence. In our study, it was found that 32% of the nurses were exposed to physical violence and 65% had psychological violence at a similar rate with other studies . In contrast, the rate of reporting physical violence was 69%.…”
Section: Discussionsupporting
confidence: 87%
“…The rate of exposure to workplace violence (WPV) is higher for nurses working in psychiatry clinics than for nurses working in other clinics . WPV ranges from verbal aggression and sexual harassment to physical attack .…”
Section: Introductionmentioning
confidence: 99%
“…It not only predicts HCW’s quality of life but also severely impacts psychological health and may lead to suicide. Recent studies report HCW who experienced MWV suffered from anxiety (25.67%), depression (28.13%), post-traumatic stress disorder symptoms (28%),22 23 poor sleep hygiene and fatigue symptoms 24…”
Section: The Impact Of Mwv In Chinamentioning
confidence: 99%
“…These aggressions favor the development of anxiety, fear, guilt, sleep disturbances, burnout, low self-perceived health status, work dissatisfaction and stress, with consequent reduction in life satisfaction 41 - 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Finland pointed out that the prevalence of nurses who experience patient aggressions is higher among professionals working in mental health settings than among those in medical or surgical settings. Working in psychiatry also includes greater odds for diagnosed depression, antidepressant medication use and sick leave due to depression and mental disorders 41 .…”
Section: Discussionmentioning
confidence: 99%